2021
DOI: 10.1002/anie.202104054
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur‐Embedded Hydrocarbon Belts: Synthesis, Structure and Redox Chemistry of Cyclothianthrenes

Abstract: Cyclothianthrenes, a series of sulphur‐embedded hydrocarbon belts proposed a decade ago, were successfully constructed through a stepwise bottom‐up synthesis. The belt [6]cyclothianthrene ([6]CT) is the smallest and most strained member of the family yet reported. Both [6]CT and [8]CT are the first examples of cyclothianthrene characterized by single crystal X‐ray diffraction. An unprecedented chiral belt [7]CT and a Möbius‐shaped [9]CT were also achieved via modular synthesis. Crystallographic and computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 61 publications
0
39
0
1
Order By: Relevance
“…On the other hand, they possess the inherent chirality of the macrocyclic figure-eight and both ( P , P )- and ( M , M )- enantiomers could be isolated by chiral high performance liquid chromatography (HPLC). It is also worthy of note that recently two double-stranded, half-twisted Möbius stripes were reported by Tanaka and Zhu et al Particularly, the latter successfully resolved the racemic isomers.…”
mentioning
confidence: 76%
“…On the other hand, they possess the inherent chirality of the macrocyclic figure-eight and both ( P , P )- and ( M , M )- enantiomers could be isolated by chiral high performance liquid chromatography (HPLC). It is also worthy of note that recently two double-stranded, half-twisted Möbius stripes were reported by Tanaka and Zhu et al Particularly, the latter successfully resolved the racemic isomers.…”
mentioning
confidence: 76%
“…131 Macrocycles 144-147 were produced with high fidelity by using a Pummerer-type fragmentation to construct the thianthrene rings after macrocycle formation. 131 Although macrocycles 144-146 adopt the expected tubular shape, compound 147, with nine thianthrene units, adopts a Möbius conformation, as observed by 1 H NMR spectroscopy. 131 The synthesis of such structures was enabled by the non-planar geometry of the thianthrene heterocycle, which significantly reduces the strain of the resulting macrocycle, as compared to carbon-based analogues.…”
Section: Review Synthesismentioning
confidence: 99%
“…Inspired by this thinking, Zhu et al recently demonstrated the synthesis of sulphur-embedded nanobelts with thianthrene moieties (Scheme 1). 13 In their initial design strategy, the introduction of thianthrene moieties would lead to dynamic nanobelts with not only reduced strain energies that originate from the bent and foldable structures of thianthrene units but also switchable complexation behaviors that originate from the redox tunable conformations of thianthrene moieties. Interestingly, in this study, the successful synthesis of a novel molecular Möbius strip was achieved.…”
Section: Nonconjugated Molecular Möbius Stripsmentioning
confidence: 99%